Stirring the Pot: Comparing Stick Input Patterns and Flight-Path Control Strategies in Airline Pilots. Issue 1 (3rd April 2018) - Haslbeck, Andreas; Hoermann, Hans-Juergen; Gontar, Patrick
ABSTRACT: Objective : This study evaluated airline pilots' inceptor input patterns and flight-path control strategies during a manual instrument approach as a function of recent flight practice. Background : Manual flying skills erode due to an extensive use of automation and rare opportunity to practice these skills. Method : One hundred and twenty-six randomly selected pilots of a European airline took part in this experiment, performing a simulated manual raw data precision approach. All of the pilots were allocated to 1 of 4 groups according to their fleet and rank: first officers and captains on short haul, as well as first officers and captains on long haul. A new method to analyze flight-path control strategies by differentiating between constant and variable flight-path errors was proposed. Time-domain measures were taken into account to evaluate sidestick inputs. Results : We distinguished between 2 different flight-path control strategies; both differed in the deviations achieved. In addition, the pilots who predominantly used 1-dimensional sidestick inputs also had smaller deviations from the ideal flight-path. Conclusion : Pilots showed a relationship between manual fine-motor flying skills and recent flight practice, especially in long-haul fleets.